Yangjing capsule improves oligoasthenozoospermia by promoting nitric oxide production through PLCγ1/AKT/eNOS pathway - Deng, Weimin; Sun, Dalin; Cai, Bin; Jin, Baofang (Frontiers in Pharmacology, 2023)
Background: Oligoasthenozoospermia is an important factor leading to male infertility. Yangjing capsule (YC), a traditional Chinese preparation, displays beneficial effects on male infertility. However, whether YC could improve oligoasthenozoospermia remains unclear. Methods: In this study, we aimed to explore the effect of YC in the treatment of oligoasthenozoospermia. Male Sprague-Dawley (SD) rats were treated with 800 mg/kg ornidazole once daily for 30 days to induce in vivo oligoasthenozoospermia; primary Sertoli cells were treated with 400 μg/mL ornidazole for 24 h to induce in vitro oligoasthenozoospermia. Results: We found that YC improved the testicle and epididymis weight, sperm concentration, sperm progressive motility, serum testosterone, fertility rate and testis morphology in ornidazole-exposed rats and enhanced cell survival in ornidazole-stimulated primary Sertoli cells. YC also inhibited the ornidazole-caused decrease in nitric oxide (NO) generation and the phosphorylation of phospholipase C γ1 (PLCγ1), AKT, and eNOS in vivo and in vitro in oligoasthenozoospermia. Furthermore, the knockdown of PLCγ1 blunted the beneficial effects of YC in vitro. Conclusion: Collectively, our data suggested that YC protected against oligoasthenozoospermia by promoting NO levels through the PLCγ1/AKT/eNOS pathway.